Method of assessment of reliability of compliance of topogeodesic security measures - Vitalii Zuiko; Serhii Zotov; Oleksandr Koshlan (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article discusses the approach to assessing the reliability of execution of topo-geodetic support measures by presenting them as a queuing system, which allows to estimate the probability of servicing the consumer with relevant information and to establish that the task performance will not be impeded due to the failure of the following input parameters: availability of topo-geodetic information in the data bank to the territory required by the consumer; availability and trouble-free operation of the communication channels through which the circulation of topo-geodetic information flows; the availability of the required number of specialists who fill the database with topo-geodetic information in accordance with the existing requirements for its accuracy, clarity and efficiency.